Economic Behavior of Traditional Market Traders in Responding to the Existence of Modern Markets and Online Markets - Dyah Ayu Suryaningrum; Eva Yuniarti Utami; Andi Naila Quin Azisah Alisyahbana (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2023)
This study aims to determine the economic behavior of traditional market traders in facing the existence of modern markets in Makassar City. This research uses qualitative research. Data collection techniques were carried out by observation, interviews, and documentation. The informants in this study were traditional market traders in Makassar City totaling 5 people as the object of research. The results of the research obtained are that the existence of modern markets greatly affects the income of traditional market traders which is marked by a drastic reduction in income. As for determining the price of traditional market traders using a bargaining system and an agreement between the seller and the buyer. In improving product quality, traditional market traders sort the goods taken from the camp to avoid damage to the product. While in improving the quality of service traditional market traders serve one by one buyers, that way buyers can also ask directly about the products to be purchased.